Compound deep drawing and extrusion process for the manufacture of geared drum. Issue 9 (June 2016) - Zhuang, Xincun; Sun, Xiaolong; Xiang, Hua; Xia, Min; Zhao, Zhen
Abstract A compound deep drawing and extrusion process was proposed in this study to produce the part like geared drum on a servo-controlled press. To improve the formability of the proposed process, the influences of various slide motions like speed motion, oscillation motion, and step motion, on the material performance were studied based on simple standard tensile test and deep drawing tests. And then, specific designed oscillation motion and step motion were adopted in compound deep drawing and extrusion process to evaluate their feasibility. The results showed that by setting a step motion at an early stage of the process, the part could not only achieve high surface quality but also reduce the extent of thickness reduction of the material.